Análisis de la metodología Scrum en gerencia de proyectos de construcción (2024)
The main purpose of this project is to study each of the advantages and compare the Scrum methodology with the traditional method. As time progresses, different types of proposals or methods are also implemented to improve the organization, duration and quality of the delivery of a construction project following their respective guidelines and requirements.